Faktor Yang Berpengaruh Terhadap Kematian Bayi Baru Lahir Di Daerah Kepulauan Alor - Adrianingsih, Narita Yuri; Hinadang, Elen A.; Dani, Andrea Tri Rian; Novitasari, Nilam (Jambura Journal of Probability and Statistics, 2024)
Binary logistic regression is an analysis that aims to determine the relationship between one or more predictor variables that are quantitative, qualitative, or a combination of both to a dichotomous response variable with two categories. Binary logistic regression analysis can also be applied in the health sector, especially in newborns' dead or alive status. Infant deaths in Indonesia, especially in the Alor Islands, are still widespread, which is due to several factors. In this study, several variables are thought to influence the status of the newborn, namely the newborn's weight, the baby's body length, the baby's gender, asphyxia, the mother's systolic blood pressure, and the mother's age at birth. The results of the analysis from this research showed that the factor that influences the death of newborn babies in the Alor Islands area is asphyxia. Newborn babies who experience asphyxia are 109,947 times more likely to die compared to babies who do not experience asphyxia.